1999
DOI: 10.1074/jbc.274.51.36403
|View full text |Cite
|
Sign up to set email alerts
|

Perlecan Mediates the Antiproliferative Effect of Apolipoprotein E on Smooth Muscle Cells

Abstract: Apolipoprotein E (apoE) is known to inhibit cell proliferation; however, the mechanism of this inhibition is not clear. We recently showed that apoE stimulates endothelial production of heparan sulfate (HS) enriched in heparin-like sequences. Because heparin and HS are potent inhibitors of smooth muscle cell (SMC) proliferation, in this study we determined apoE effects on SMC HS production and cell growth. In confluent SMCs, apoE (10 g/ml) increased 35 SO 4 incorporation into PG in media by 25-30%. The increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
3
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 58 publications
5
43
3
1
Order By: Relevance
“…It is not possible to conclude if it is a reduced apoE level in obese adults which leads in part to low grade inflammation, expressed by increased CRP level or, inversely, if it is low grade systemic inflammation which leads to reduced apoE level. However, in vitro cellular studies have suggested an anti-proliferative role of apoE on T lymphocytes, 45,55 smooth muscle cells 44,46 and microglia. 47 Indirect in vivo anti-inflammatory role of apoE has also been suggested in apoE knock-out mice model.…”
Section: Discussionmentioning
confidence: 99%
“…It is not possible to conclude if it is a reduced apoE level in obese adults which leads in part to low grade inflammation, expressed by increased CRP level or, inversely, if it is low grade systemic inflammation which leads to reduced apoE level. However, in vitro cellular studies have suggested an anti-proliferative role of apoE on T lymphocytes, 45,55 smooth muscle cells 44,46 and microglia. 47 Indirect in vivo anti-inflammatory role of apoE has also been suggested in apoE knock-out mice model.…”
Section: Discussionmentioning
confidence: 99%
“…ApoE effects on proteoglycans in different pools, pericellular (trypsinreleasable representing cell surface and extracellular proteoglycans), cellular (Triton X-100/NH 4 releasable), and matrix (guanidine hydrochloride extractable following Triton X-100 treatment), were determined as described previously (18). Pericellular proteoglycans minus matrix proteoglycans was represented as cell surface proteoglycans.…”
Section: Methodsmentioning
confidence: 99%
“…Cell Proliferation-Cell proliferation was assessed by [ 3 H]thymidine incorporation as described previously (18). Mesangial cells were seeded at a density of 2 ϫ 10 4 /well in a 48-well plate, and experiments were performed the following day (40 -50% confluency).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential growth suppressor is perlecan, a large heparan sulfate proteoglycan that is expressed in most extracellular matrixes and basement membranes (148). Perlecan has been shown to inhibit in vitro SMC proliferation (149,150), adhesion (151) and migration (152). In vivo, perlecan has been shown to inhibit thrombosis and intimal hyperplasia after arterial injury (153).…”
Section: Perlecanmentioning
confidence: 99%